Analisis Hukum Penghasilan Content Creator YouTube dalam Perspektif Fiqih Muamalah: Studi Kasus Monetisasi dan Endorsement - Metriadi (Mutawasith: Jurnal Hukum Islam, 2025)
The development of digital technology has created new income opportunities through the YouTube platform for content creators, but the Islamic legal aspects of monetization and endorsement practices still require an in-depth study from the perspective of fiqh muamalah. This study aims to identify the forms of contracts in YouTube monetization, analyze their compatibility with muamalah principles, and formulate sharia guidelines for Muslim content creators. The research method uses a qualitative approach with case studies, content observations, and documentation studies. The data analysis uses an interactive model with a framework of contemporary Islamic law analysis that considers aspects of the contract, conformity with the principle of muamalah, legal status of sources of income, impact evaluation, and formulation of sharia guidelines. The results of the study show that income from YouTube monetization can be categorized as halal with certain conditions. The practice of monetization can be qiyas, with ijarah and ju'alah contracts, while endorsements require adherence to the principles of honesty and transparency. The research provides practical guidance for Muslim content creators in carrying out sharia-compliant monetization activities as well as theoretical contributions in the development of contemporary fiqh muamalah fiqh.